1995
DOI: 10.1037/0735-7044.109.3.404
|View full text |Cite
|
Sign up to set email alerts
|

8-OH-DPAT microinjected in the region of the dorsal raphe nucleus blocks and reverses the enhancement of fear conditioning and interference with escape produced by exposure to inescapable shock.

Abstract: Prior work suggests that inhibition of the dorsal raphe nucleus (DRN) either during exposure to inescapable electric shock (IS) or during later behavioral testing might block the usual behavioral consequences of IS. The 5-HT1A agonist 8-OH-DPAT was microinjected into the region of the DRN either before exposure to IS or before testing for fear conditioning and escape learning conducted 24 hr later. IS potentiated fear conditioning and interfered with escape performance. These effects were completely prevented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
127
1
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 146 publications
(136 citation statements)
references
References 46 publications
(89 reference statements)
5
127
1
3
Order By: Relevance
“…Furthermore, evidence shows that prior exposure to acute or chronic stressors can result in behavioral and pharmacological sensitization effects caused by changes dopaminergic (Pani et al, 2000;de Jong et al, 2005) and serotonergic tone (Adell et al, 1988;Chung et al, 2000;Matuszewich and Yamamoto, 2003). In support of this view, Watkins and Maier have shown that the habenula is essential for the normal sensitization of DRN neurons after uncontrollable stress (Maier et al, 1995;Maswood et al, 1998;Grahn et al, 1999;Amat et al, 2001). The stress-induced alteration in the habenulo-DRN pathway results in increase excitation of DRN 5-HT neurons and changes in subsequent stress behaviors.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, evidence shows that prior exposure to acute or chronic stressors can result in behavioral and pharmacological sensitization effects caused by changes dopaminergic (Pani et al, 2000;de Jong et al, 2005) and serotonergic tone (Adell et al, 1988;Chung et al, 2000;Matuszewich and Yamamoto, 2003). In support of this view, Watkins and Maier have shown that the habenula is essential for the normal sensitization of DRN neurons after uncontrollable stress (Maier et al, 1995;Maswood et al, 1998;Grahn et al, 1999;Amat et al, 2001). The stress-induced alteration in the habenulo-DRN pathway results in increase excitation of DRN 5-HT neurons and changes in subsequent stress behaviors.…”
Section: Discussionmentioning
confidence: 95%
“…[1,24]). IS in one environment later increases freezing immediately after footshock in a different environment and interferes with shuttlebox escape, but ES has no effect [22].…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which ES could block or reduce later IS effects on social exploration and sucrose preference is unknown. With regard to neural mediation ,IS-induced changes in post-shock freezing and shuttle escape depend upon dorsal raphé nucleus (DRN) activation at the time of IS [24], this activation being prevented by behavioral control [1] (for review see [26]). The role of the DRN has only been examined with escape and freezing to shock as measures.…”
Section: Introductionmentioning
confidence: 99%
“…For example, exposure to inescapable shock (IS) but not equal amounts and durations of escapable shock (ES) leads to later failure to learn to escape shocks in a different situation (Maier and Seligman, 1976). Other behavioral outcomes resulting from exposure to IS but not ES include an exaggeration of fear conditioning to a context (Maier et al, 1995), increases in neophobia (Minor et al, 1994), and reductions in social interaction (Short and Maier, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Activation and sensitization of serotonergic (5-HT) neurons in the dorsal raphe nucleus (DRN) is necessary for producing the behavioral effects of uncontrollable stress (Maier et al, 1995). Sensitization of DRN 5-HT neurons occurs because IS, relative to ES, selectively activates DRN 5-HT neurons (Grahn et al, 1999).…”
Section: Introductionmentioning
confidence: 99%